A Taiwanese Nationwide Cohort Study Shows Interferon-Based Therapy for Chronic Hepatitis C Reduces the Risk of Chronic Kidney Disease. Issue 32 (August 2015) - Chen, Yi-Chun; Hwang, Shang-Jyh; Li, Chung-Yi; Wu, Chia-Pin; Lin, Li-Chu; Pavlos, Malindretos.
<x xml:space="preserve">Abstract</x> Abstract Hepatitis C virus (HCV) infection is a risk factor for chronic kidney disease (CKD). However, it remains unclear whether interferon-based therapy (IBT) for HCV was associated with reduced risk of CKD. From the Taiwan National Health Insurance Research Database, we identified 919 patients who received 3 months or more of IBT as our treated cohort. This cohort was propensity score-matched 1:4 with 3676 controls who had never received IBT for HCV infection (untreated cohort). Cumulative incidences of and hazard ratios (HRs) for CKD were calculated after adjusting for competing mortality. In the matched HCV cohort, the risk of CKD was significantly lower in the treated cohort (7-year cumulative incidence, 2.6%; 95% confidence interval [CI], 0.7%–6.9%) than in the untreated cohort (4%; 95% CI, 3.5%–5.2%) (P < 0.001), with an adjusted HR of 0.42 (95% CI, 0.20–0.92; P = 0.03). The results also held in the overall HCV cohort. The number needed to treat for 1 fewer CKD at 7 years was 58. The reduced risk of CKD was greatest (0.35; 0.14–0.87; P = 0.024) in HCV-infected patients who received 6 months or more of IBT. Multivariable stratified analysis verified that greater risk reduction of CKD was present in HCV-infected patients with hyperlipidemia, diabetes, hypertension, and those without coronary heart disease. In conclusion, IBT, especially for 6 or more months, is associated with reduced risk of CKD in HCV-infected patients. Hyperlipidemia, diabetes, hypertension, and coronary heart disease can modify this association.